Developing a Python program for value investing with an English interface - Khor, Daryl Yong Xin (Nanyang Technological University, 2024)
"Developing a Python Program for Value Investing with an English Interface" aims to bridge the gap between traditional value investing principles and modern technology. Value investing, popularized by renowned investor Warren Buffett, involves analysing a company's fundamentals to identify undervalued stocks with significant growth potential. Discounted Cash Flow Model is one of the value investing principles he has continuously brought up in all Berkshire Hathaway conferences. While Buffett relies on manual analysis, this project seeks to leverage the power of Python programming to automate the stock selection process, enabling investors to make informed choices.